2019
DOI: 10.1016/j.jgr.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng (Korea Red Ginseng) repairs diabetic sensorineural damage through promotion of the nerve growth factor pathway in diabetic zebrafish

Abstract: Background Diabetic sensorineural damage is a complication of the sensory neural system, resulting from long-term hyperglycemia. Red ginseng (RG) has shown efficacy for treatment of various diseases, including diabetes mellitus; however, there is little research about its benefit for treating sensorineural damage. Therefore, we aim to evaluate RG efficacy in alloxan-induced diabetic neuromast (AIDN) zebrafish. Methods In this study, we developed and validated an AIDN ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Repeated SiO 2 as well ODS c.c. for FKE and FKB 13 C-3), 146.7 (C-3′)] correlated respectively, indicating two methoxies existed in C-3 and C-3′. Therefore, 3 was identified as (-)-matairesinol, which was affirmed through comparing spectroscopic data in literature [30].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Repeated SiO 2 as well ODS c.c. for FKE and FKB 13 C-3), 146.7 (C-3′)] correlated respectively, indicating two methoxies existed in C-3 and C-3′. Therefore, 3 was identified as (-)-matairesinol, which was affirmed through comparing spectroscopic data in literature [30].…”
Section: Resultsmentioning
confidence: 72%
“…Alloxan (AL), which damages the pancreas by β-cells preventing from producing insulin, has been used as diabetogenic agent on in vivo experiments [11]. Previously, AL has reported to induce diabetes and diabetic complications on the ZF model by morphological observation [12,13]. Our preliminary study revealed Forsythia koreana flowers MeOH extract (FKFM) increased PI size damaged by AL in ZF.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Flavonoids, alkaloids, phenolic compounds, terpenoids, saponins, and phytosterol-type constituents of herbal medicines used worldwide are being actively studied as new drug candidates for the treatment of various diabetic complications [ 17 ]. Among these, East Asian herbal medicine (EAHM) is an area of natural medicine in which therapeutic candidates for DPN have been the most actively investigated [ 10 , 12 , 18 , 19 , 20 , 21 ]. EAHM is a generic term for natural materials used as medicines for the treatment of diseases in many countries in East Asia, including Korea, China, Taiwan, and Japan, and the study thereof [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Red ginseng provided during the process of steaming, and dried white ginseng provided by air‐drying (Karmazyn et al., 2011 ). Red ginseng has shown efficacy for the remedy of a wide range of disorders including hyperglycemia (Nam et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%